Cardioprotective effects of azilsartan compared with that of telmisartan on an in vivo model of myocardial ischemia‐reperfusion injury. Issue 7 (16th April 2021) - Garg, Shanky; Khan, Sana Irfan; Malhotra, Rajiv Kumar; Sharma, Manish Kumar; Kumar, Manoj; Kaur, Punit; Nag, Tapas Chandra; Ray, Ruma; Bhatia, Jagriti; Arya, Dharamvir Singh
Abstract: Azilsartan is found to be more potent than other angiotensin receptor blockers in reducing blood pressure. However, its effect on the heart following myocardial infarction remains to be established. For the first time, we investigated the peroxisome proliferator‐activated receptor‐γ (PPAR‐γ) agonistic and cardioprotective properties of azilsartan. Computational modeling studies of interactions between azilsartan and PPAR‐γ revealed azilsartan as an agonist of PPAR‐γ and showed the mechanism of azilsartan in cardioprotection. Our study compared the cardioprotective potential of telmisartan to that of azilsartan in a murine model of myocardial ischemia‐reperfusion injury by comparing their antioxidant, ant apoptotic, anti‐inflammatory, mitogen‐activated protein kinase (MAPK)‐modulating ability, and PPAR‐γ agonistic activity. Male Wistar rats were grouped into four to receive vehicle (dimethyl sulfoxide [0.05%] 2 ml/kg) telmisartan (10 mg/kg p.o.), azilsartan (10 mg/kg p.o.) or azilsartan with specific PPAR‐γ blocker, GW 9662 for 28 days. Ischemia was induced for 45 min on the 29th day followed by 60 min of reperfusion. Telmisartan and azilsartan pretreatment significantly nearly normalized cardiac parameters and preserved structural changes. Both drugs inhibited oxidative burst, inflammation, as well as cell death by modulating apoptotic protein expression along with reduction in 4′, 6‐diamidino‐2‐phenylindole/terminal deoxynucleotidyl transferase dUTP nick end labeling‐positive cells. An increment in pro‐survival kinase ERK paralleled with a reduction in p38 and JNK was also revealed by MAPK pathway studies, after administration of these drugs. Interestingly, the aforementioned changes induced by both drugs were reversed by administration of the specific PPAR‐γ antagonist, GW9662. However, we found that azilsartan upregulated PPAR‐γ to a lesser extent as compared to telmisartan and the latter may be preferred in hypertensive patients at risk of myocardial infarction.